Bacillus subtilis and Bifidobacteria bifidum Fermentation Effects on Various Active Ingredient Contents in Cornus officinalis Fruit - Xiuren Zhou; Yimin Zhao; Lei Dai; Guifang Xu (Molecules, 2023)
Microbial fermentation has been widely used to improve the quality and functional composition of food and edibles; however, the approach has rarely been applied to traditional Chinese medicines. In this study, to understand the effect of microbial fermentation on the active ingredients of traditional Chinese medicines, we used Bifidobacterium bifidum and Bacillus subtilis to ferment the traditional Chinese medicine, Cornus officinalis fruit (COF), and determined the levels of active ingredients using HPLC (high-performance liquid chromatography). According to the results, both B. subtilis and B. bifidum substantially increased the amount of gallic acid in the COF culture broth after fermentation; however, the two species of bacteria had no effect on the loganin content. Moreover, the B. subtilis fermentation reduced the contents of ursolic acid and oleanolic acid in the COF broth, whereas the B. bifidum fermentation did not. This study contributes to a better understanding of the mechanism by which microbial fermentation alters the active ingredient levels of traditional Chinese medicines, and suggests that fermentation may potentially improve their functional ingredients.